Nematicidal Activity of Cyclopiazonic Acid Derived From Penicillium commune Against Root-Knot Nematodes and Optimization of the Culture Fermentation Process - Nguyen, Van Thi; Yu, Nan Hee; Lee, Yookyung; Hwang, In Min; Bui, Hung Xuan; Kim, Jin-Cheol (Frontiers in Microbiology, 2021)
Among 200 fungal strains isolated from the soil, only one culture filtrate of Aspergillus flavus JCK-4087 showed strong nematicidal activity against Meloidogyne incognita. The nematicidal metabolite isolated from the culture filtrate of JCK-4087 was identified as cyclopiazonic acid (CPA). Because JCK-4087 also produced aflatoxins, six strains of Penicillium commune, which have been reported to be CPA producers, were obtained from the bank and then tested for their CPA productivity. CPA was isolated from the culture filtrate of P. commune KACC 45973; its EC50-3 days ¬values against second-stage juveniles of M. incognita, M. hapla, and M. arenaria were 4.50, 18.82, and 60.51 µg mL-1, respectively. The cumulative percent of egg hatch of the three root-knot nematode species exposed to CPA was significantly reduced after a total of 28 days of treatment. The enhancement of CPA production by P. commune KACC 45973 was explored using an optimized medium based on Plackett–Burman design (PBD) and central composite design (CCD). The highest CPA production (381.48 µg mL-1) was obtained from the optimized medium, exhibiting an increase by 7.88 times when compared with that from potato dextrose broth culture. Application of the wettable power-type formulation of the ethyl acetate extract of the culture filtrate of KACC 45973 reduced gall formation and nematode populations in tomato roots and soils. These results suggest that CPA produced by P. commune KACC 45973 can be used as either a biochemical nematicide or a lead molecule for developing new chemical nematicides to control root-knot nematodes.